Computed tomographic study in young epileptics in Kashmir, India - Mohd Ashraf; Mohd Irshad; Javed Chowdhary; Reyaz A Malla; Yasmeena Akhter (Al Ameen Medical College, 2013)
Background: Infectious diseases like neurocysticercosis and neurotuberculosis are endemic in Indian subcontinent and are important causes of epilepsy. Epileptic children are prone to have poor school performance, higher levels of anxiety and depression apart from low self esteem. These treatable condition could be easily picked up on neuroimaging like cranial computed tomography (CT) scan and treated accordingly at an earliest. Objectives: To assess the role of cranial computed tomography scan in children having epilepsy. Material and Methods: Seventy two children between the age of 1 month and 14 years were prospectively enrolled, who had atleast two unprovoked seizures greater than 24 hours apart, and all those children where seizures result from acute central nervous system insult were meticulously excluded. Diagnosis of epilepsy was based on detailed history, thorough clinical examination, routine laboratory tests with additional specific tests like electroencephalogram (EEG) and CT scan brain. Results: Males constituted 62.5% and females 37.5% of our sample (p=0.247). The EEG was abnormal in 68.1% of all subjects, among which EEG was abnormal in 69.8% of generalized seizures, 64.7% in partial seizures and 1% in undetermined seizures. The spectrum of various seizure types in our study was generalized seizures in 73.6%, partial seizures in 23.6% & undetermined seizures in 2.8%. The incidence of these lesions in hospitalized young epileptics was 31.9%, in order of their frequency, it was cerebral atrophy and dilated ventricle (18.8% each); calcifications (15.5%); encephalomalacia and pachygyria (9.4% each); HIE changes, tuberous sclerosis (6.3% each); leucodystrophy, thin corpus callosum, large cisterna magna, granuloma and periventricular leukomalacia (3.1% each). The intracranial structural lesions were present in 22.6% of generalized seizures, 64.7% of partial seizures, none of undetermined seizures (p=0.004). Conclusion: Abnormal cranial CT scan were more commonly seen in patients having remarkable family and personal history, abnormal clinical details, partial seizures and persistent altered sensorium or neurodeficit